The unintended real effects of short selling in an emerging market - Ni, Xiaoran; Yin, Sirui (Journal of Corporate Finance, 2020)
Exploiting the staggered removal of short-sale bans in China, we document unintended real effects of allowing short selling in an emerging market featured by concentrated ownership and weak investor protection. Pilot firms have worse short-term and long-term market performances after the removal of short-sale bans. Additionally, pilot firms undertake less risk and have worse performance following the launch of the program. The effect is stronger when controlling shareholders' private benefit is large and when corporate governance is weak. Faced with increased short selling threats, pilot firms cut capital investments and R&D expenditures, reduce equity financing, and lower debt ratios. Contrary to prior studies showing that short selling encourages value-enhancing risky investments in developed markets, our findings suggest that in emerging markets such as China, short selling can result in value losses by inducing firms to forgo profitable risky projects.